THE IMPACT OF LIQUIDITY RISK AND MACROECONOMIC FACTORS ON THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS IN MALAYSIA - Stephen, Masturani; Ting , Mei Fei; Ng , Wen Hui Irene; Abdul Karim, Bakri; Zaidi, Nurul Syuhada; Khalid, Farah Dipah binti (UNIMAS Review of Accounting and Finance, 2025)
This study aims to examine the impact of liquidity risk and macroeconomics factors on the financial performance of commercial banks in Malaysia. This study uses secondary data from 20 commercial banks in Malaysia from 2019 to 2023 and panel data estimation. The empirical results show that the loan-to-deposit ratio has a significant negative impact on return on assets. Interest rates and GDP also shows significant positive effects on bank performance, highlighting the role of macroeconomic conditions in influencing profitability. In contrast, capital adequacy ratio and current ratio had insignificant effects on profitability. This study provides practical insights for policymakers, investors, and bank managers in enhancing risk management and decision-making processes.